On the Specifics of Studying Organized Crime at the Present Stage - KOILYBAYEV, Medet T.; DILBARKHANOVA, Zhanat R. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).24, 2020)
This article studies the key aspects of combating organized crime at the present stage. Based on the analysis conducted, the authors describe organized crime as a complex, criminally legal and social phenomenon. They provide their understanding of organized crime, its causes and conditions, as well as indicate possible social consequences. Within the context of the article, the authors prove the difficulty of counteracting the phenomenon and emphasize its social danger since it undermines the foundations for the well-being of the Kazakh society. The scale and growth rate of organized crime in recent decades has turned it into one of the main factors hindering the country's economic and social development, causing civil mistrust in the law enforcement system and government bodies at all levels; therefore, citizens of Kazakhstan are anxious about their life and well-being. The article provides suggestions on studying modern organized crime based on both the international and Kazakh experience. From the perspective of general science, this article conducts studies in the field of criminology and criminal law and contributes to the methodological enrichment of the phenomenon of organized crime in theoretical and practical aspects. This approach helps better understand this phenomenon, determine its typical features and develop and apply countermeasures. At the same time, the authors do not claim a monopoly of absolute truth but rather attempt to study organized crime from a new perspective, which allows dwelling on the essence of this social phenomenon.